2018
DOI: 10.1155/2018/7540587
|View full text |Cite
|
Sign up to set email alerts
|

Loss to Follow-Up among HIV Positive Pregnant and Lactating Mothers on Lifelong Antiretroviral Therapy for PMTCT in Rural Uganda

Abstract: Background. Mother-to-Child Transmission of HIV accounts for more than 90% of all pediatric HIV infections. However, Prevention of Mother-to-Child Transmission (PMTCT) of HIV through provision of lifelong ART to HIV positive mothers faces various challenges which affect its success. One of such challenges is the loss to follow-up (LTFU) of mothers. Methodology. We conducted a cross-sectional study utilizing both quantitative and qualitative data collection methods. We were able to trace 279 HIV positive, pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 13 publications
6
32
2
Order By: Relevance
“…Among these measures, increasing trained human power including midwives, frequent follow-up schedule and better drug preparation ( xed dose ART treatment) by giving better consideration for mothers to implement the program effectively (40). The current study nding is also lower than studies conducted in different African countries such as Uganda (15,16,18), South Africa(24), Malawi (14,46) and Kenya (19).This discrepancy might be due to the difference in study time, operational de nition of the outcome variable, and characteristic of study participants. For example, the study period for a study conducted in Malawi was 3-years record review (14) whereas the current study incorporated recent years' data which had better improvement ART coverage.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Among these measures, increasing trained human power including midwives, frequent follow-up schedule and better drug preparation ( xed dose ART treatment) by giving better consideration for mothers to implement the program effectively (40). The current study nding is also lower than studies conducted in different African countries such as Uganda (15,16,18), South Africa(24), Malawi (14,46) and Kenya (19).This discrepancy might be due to the difference in study time, operational de nition of the outcome variable, and characteristic of study participants. For example, the study period for a study conducted in Malawi was 3-years record review (14) whereas the current study incorporated recent years' data which had better improvement ART coverage.…”
Section: Discussioncontrasting
confidence: 69%
“…Supportive ndings were reported from previous studies in Ethiopia and Brazil (10,30,48). Possible explanations for this might be remote area mothers are forced to travel long distances in order to get the nearest hospital, which necessarily involves high costs which leads LTFU (16) and cannot easily get transport services due to poor /lack of road construction, makes women to walk long distances by bare foot, this leads them less likely to adhere to option B+ strategy (31) and resulting in missing the appointments (15,32). This justi cation is also supported by the report given that lack of access to health care service leads to poor adherence and LTFU to option B+ PMTCT drugs (15).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Monitoring adherence and retention for mothers on Option B+ were a big challenge and information had shown that there was substantial LTFU in Uganda (33). A transport costs above $2.75, waiting time greater than 1 hour, and perception that the child is already infected were associated with loss to follow-up, but mothers knowledge that ARV drugs work was protective for LTFU (34).…”
mentioning
confidence: 95%